Chemical-genetic profiling reveals limited cross-resistance between antimicrobial peptides with different modes of action - Bálint Kintses (Nature Portfolio, 2019)
The genetics underlying bacterial susceptibility to antimicrobial peptides (AMPs) remain unclear. Here, using a genome-wide chemical-genetic approach, the authors map the diversity of resistance determinants across AMPs in Escherichia coli and provide evidence that cross-resistance is prevalent only between AMPs with similar modes of action.